Population and Housing (Mis)match in Lisbon, 1981–2018. A Challenge for an Aging Society - Garha, Nachatter Singh (2021)
Over the past four decades, Lisbon’s population has witnessed some notable changes in its growth, age structure, conjugal patterns and ethnic diversity. These changes have affected the size, composition and structure of households, which in turn modified the demand for housing in Lisbon. At the same time, some changes were also made to the housing stock, especially in size, but also in the replacement of small apartment buildings with large residential apartment blocks. However, the discrepancies between demographic changes and the housing stock have created new challenges for the housing market in Lisbon to provide adequate housing to all households in the city. Using data from the 1981–2011 census obtained from IPUMS International, population estimates from the National Institute of Statistics (INE) and other secondary sources, this article identifies and measures the magnitude of (mis)matches between existing housing stock and housing needs of the population in Lisbon. Theoretically, this article adds to the knowledge about the relationship between population and housing dynamics in large cities. Empirically, it provides evidence on the existence and magnitude of (mis)matches in Lisbon’s housing market and explores the underlying dynamics behind them. Lastly, it offers some policy tools and recommendations to address these (mis)matches.